Curriculum for Development of Professional Manpower for Secondary Information Work and Service - Bhattacharyya, G. (Journal of Information and Knowledge, 2014)
Discusses the need for adaptation of the knowledge and skills of information professional to the changing information environment. Identifies the secondary information work and service as the domain of information professionals. Delineates the variety of knowledge and services needed for appropriate utilisation of information technology in the contemporary library and information systems and services. Provides a curriculum for Information technology for Ubrary and information professionals.